Seizure phenotypes and short-term prognosis in neonatal lupus: a multicenter retrospective cohort in China - Sun, Wenqiang; Jin, Xinyun; Li, Yihui; Liu, Xue; Zhu, Linzhou; Zhou, Minqian; Xie, Zhirong; Li, Lili; Yu, Yanliang; Jiang, Yue; Hu, Jinhui; Huo, Jie; et al. (Frontiers in Immunology, 2026)
ObjectivesNeonatal lupus erythematosus (NLE) is an antibody-mediated autoimmune disorder that can affect neurologic outcomes. Seizures are an uncommon but clinically important phenotype. This study assessed clinical features, neuroimaging findings, and short-term outcomes in infants with NLE and seizures.MethodsWe conducted a multicenter retrospective cohort study of infants with NLE admitted to seven tertiary centers in China. Infants were categorized as epileptic seizures (ES), non-epileptic CNS involvement (NE), or no CNS involvement (nCNS). Maternal characteristics and medications during pregnancy, infant clinical manifestations, laboratory indices, autoantibodies, EEG findings, and neuroimaging were extracted from medical records. Group comparisons and multivariable logistic regression were performed to identify factors associated with ES. Follow-up was conducted to 6 months of age.ResultsAmong 246 infants with NLE, 17 (6.91%) had seizures, 39 (15.85%) had non-seizure CNS involvement, and 190 (77.24%) had no CNS involvement. All ES infants presented with acute symptomatic seizures, predominantly focal. Neuroimaging abnormalities were common, most frequently intracranial hemorrhage. Anti-SSA/Ro positivity was universal in ES cases and significantly higher than in nCNS (P < 0.05). Maternal hydroxychloroquine (HCQ) use was less frequent in ES than nCNS (P < 0.05). Regarding organ involvement, the ES group showed higher rates of thrombocytopenia, coagulation abnormalities, hypocomplementemia, and pancytopenia than the nCNS group, as well as higher frequencies of hypocomplementemia and pancytopenia compared with the NE group (all P < 0.05). Multivariate regression analysis revealed that maternal HCQ use during pregnancy was independently associated with a lower odds of ES (OR: 0.066, 95% CI: 0.015–0.288, P = 0.001). No recurrent seizures were observed in neonates in the ES group after hospital discharge. However, nine infants exhibited varying degrees of developmental delay.ConclusionsNLE infants with seizures often exhibit focal seizures and structural brain injury, associated with anti-SSA/Ro positivity, limited maternal HCQ exposure, and hematologic abnormalities. Despite good seizure control, developmental delay was frequent, indicating risk for adverse neurodevelopment.